The Impact of Market Sentiment on Business Fixed Investment in Malaysia - Z.A., Karim; A.Y., Yusoff; Bakri, Abdul Karim; Norlin, Khalid (SpringerLink, 2024)
Understanding how market sentiment reflects the firm investment decision (capital expenditure) is crucial for businesses to make a proper investment strategy. This is because investor sentiment and firms’ investment decision-making lie behind the reasoning that a firm’s investment selection forms the most crucial part of its overall business decisions. Thus, this study examines how market sentiment, measured by Business Condition Index (BCI) and Consumer Sentiment Index (CSI), reflects Malaysian firms’ investment from 2000 to 2018. This study applies a system generalised method of moment (GMM) technique with 673 firms’ unbalanced panel data. Due to global uncertainty and market downturn, an investor’s confidence level can change from optimism to infectious pessimism. When the market is pessimistic, investors’ confidence becomes negative, leading to a decline in capital expenditure (CAPEX). The findings show that both market sentiment indicators significantly influence private firms’ investment. Higher market sentiment indices create optimism for firms and increase business fixed investment.